2011
DOI: 10.1002/jclp.20777
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a trauma focused spiritually integrated intervention for veterans exposed to trauma

Abstract: Building Spiritual Strength (BSS) is an 8-session, spiritually integrated group intervention designed to address religious strain and enhance religious meaning making for military trauma survivors. It is based upon empirical research on the relationship between spirituality and adjustment to trauma. To assess the intervention's effectiveness, veterans with histories of trauma who volunteered for the study were randomly assigned to a BSS group (n = 26) or a wait-list control group (n = 28). BSS participants sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 55 publications
(33 reference statements)
1
131
0
Order By: Relevance
“…Several recent intervention efforts highlight these possibilities. For example, Harris and colleagues (Harris et al, 2011) have developed a trauma-focused, spiritually-integrated intervention and demonstrated promising initial findings for helping veterans alleviate negative religious coping and resolve spiritual struggles. Taking another approach, Bormann and colleagues (Bormann, Thorp, Wetherell, Golshan, & Lang, 2013) demonstrated that mantram meditation reduced PTSD symptoms among veterans, and that the improvements were mediated by increasing spiritual well-being (Bormann, Liu, Thorp, & Lang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent intervention efforts highlight these possibilities. For example, Harris and colleagues (Harris et al, 2011) have developed a trauma-focused, spiritually-integrated intervention and demonstrated promising initial findings for helping veterans alleviate negative religious coping and resolve spiritual struggles. Taking another approach, Bormann and colleagues (Bormann, Thorp, Wetherell, Golshan, & Lang, 2013) demonstrated that mantram meditation reduced PTSD symptoms among veterans, and that the improvements were mediated by increasing spiritual well-being (Bormann, Liu, Thorp, & Lang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, when focusing on the Stable High PTSD group in particular, many of these patients might have been struggling to resolve other salient traumas (e.g., killing, atrocities) that were not captured by the traditional combat exposure measure used in this study. Several researchers have piloted interventions that may address shame/guilt and other dimensions of moral injury in evidence-based treatments for combat-related PTSD [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Results of studies are equivocal regarding trauma's negative or positive effects on an individual's religious beliefs and behaviors [12][13][14][15][16]. Harris et al developed an intervention called Building Spiritual Strength (BSS) to assist those who experienced military trauma in reducing PTSD symptoms by exploring spirituality as a source of support [17]. This 8 wk (2 h/wk) interfaith group intervention was designed to help participants find meaning in their traumatic experiences and to minimize distress resulting from a disconnection with their Higher Power.…”
Section: Introductionmentioning
confidence: 99%